2009
DOI: 10.1111/j.1365-2702.2008.02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Surviving a life‐threatening crisis: Taiwan’s nurse leaders’ reflections and difficulties fighting the SARS epidemic

Abstract: Nurse leaders become important executors of intervention in this health disaster, requiring emotional intelligence to manage their internal conflicts and interpersonal relationships effectively. They developed sociopolitical and analytical abilities and crucial requirements for planning and implementing strategies in areas where none previously existed. Building support systems was an important resource for managing conflicts between familial and professional roles. Relevance to clinical practice. Findings wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(147 citation statements)
references
References 28 publications
3
137
0
6
Order By: Relevance
“…The events focused on were the SARS outbreak (Chung, Wong, Suen, & Chung, 2005;Liu & Liehr, 2009;Shih et al, 2007Shih et al, , 2009, the H1N1 pandemic (Lam & Hung, 2013), nonspecified emerging respiratory infectious disease outbreaks (Koh, Hegney, & Drury, 2012) and nonspecified epidemic events (O'Boyle, Robertson, & Secor-Turner, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The events focused on were the SARS outbreak (Chung, Wong, Suen, & Chung, 2005;Liu & Liehr, 2009;Shih et al, 2007Shih et al, , 2009, the H1N1 pandemic (Lam & Hung, 2013), nonspecified emerging respiratory infectious disease outbreaks (Koh, Hegney, & Drury, 2012) and nonspecified epidemic events (O'Boyle, Robertson, & Secor-Turner, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006). Two studies employed a two-step within-method qualitative triangulation design (Shih et al, 2007(Shih et al, , 2009; one study adopted a phenomenological approach ; one study used a descriptive exploratory method (Liu & Liehr, 2009); and three studies adopted a simple qualitative design (Koh et al, 2012;Lam & Hung, 2013;O'Boyle et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Chung et al (2005) Regarding the workplace resources that were associated with nurses' preparedness, the importance of a supportive relationship among coworkers in the work environment is noted in four of the selected studies Liu & Liehr, 2009;Shih et al, 2007Shih et al, , 2009). Chung et al (2005) identified that nurses were motivated by an atmosphere of "non-hierarchical team spirit" (p. 515) across multiple disciplines in the workplace, which resulted in a greater intention to respond to an epidemic event, as a high degree of collegiality would be generated in such conditions.…”
Section: Professional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…9,15 The research literature suggests that leaders who manage a crisis effectively tend to be emotionally intelligent. 16 They also have the innate ability to think globally and understand the interdependencies and patterns of different components of a larger structure or system. Last, they can synthesize information and communicate imperatives in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Last, they can synthesize information and communicate imperatives in a timely manner. 9,15,16 One of the first studies of nurse leaders in crisis situations was done by Shih and colleagues, 16 who studied the experiences of nurse leaders and the survival strategies employed by them during the SARS epidemic. Based on the data gathered from focus-group interviews and an open-ended questionnaire, the authors identified that nurse leaders are important facilitators of interventions in health disasters.…”
Section: Introductionmentioning
confidence: 99%